The effects of replacement Metakaolin with diatomite in geopolymer materials - Suwanan Thammarong (2019)
© 2019 Trans Tech Publications, Switzerland. Geopolymers are aluminosilicate inorganic polymers. In this study, the effects of replacement metakaolin with diatomite in geopolymer materials were investigated. The geopolymer materials were prepared by leaching diatomite (from Lampang province) and metakaolin (from Ranong province) with alkaline activator solutions. The fresh slurry was cast into plastic molds with a cubic shape and then cured at room temperatures. Effects of ratios between diatomite and metakaolin were investigated. Furthermore, influences of curing time on the properties of the studied samples were also determined. Many techniques for material characterization such as XRF, XRD, and SEM were employed in this work. The mechanical property of geopolymer compressive strength was tested after curing. It was found that compressive strength of the samples increased with increased amounts of diatomite.